Interleukin 1 induces a shock-like state in rabbits. Synergism with tumor necrosis factor and the effect of cyclooxygenase inhibition. - Okusawa, S (1988)
In addition to activating T and B lymphocytes, interleukin 1 (IL-1) induces several hematologic and metabolic changes typical of host responses to infection and injury. We now report a new biological property, namely, the induction of hypotension. Rabbits given a single intravenous injection of recombinant human IL-1-beta (5 micrograms/kg) rapidly developed decreased systemic arterial pressure, which reached the lowest levels after 50-60 min and slowly returned to pre-IL-1 values after 3 h. Associated with the hypotension, systemic vascular resistance and central venous pressure fell, while cardiac output and heart rate increased. These responses were prevented by ibuprofen given 15 min before the IL-1. A bolus injection of IL-1 followed by a 2-h infusion sustained the hypotension and was associated with leukopenia and thrombocytopenia. Ibuprofen given at the mid-point of the infusion reversed the changes in all hemodynamic parameters, but had no effect on the leukopenia or thrombocytopenia. Tumor necrosis factor (TNF) also induced a shock-like state in rabbits. When the dose of IL-1 or TNF was reduced to 1 microgram/kg, no hemodynamic changes were observed; however, the combination of these low doses of both cytokines resulted in a profound shock-like state including histological evidence of severe pulmonary edema and hemorrhage. Pretreatment with ibuprofen prevented the hemodynamic, leukocyte, and platelet changes induced by the low-dose cytokine combination, and ameliorated the pulmonary tissue damage. These results demonstrate that IL-1, like TNF, possesses the ability to induce hemodynamic and hematological changes typical of septic shock, and that the combination of IL-1 and TNF is more potent than either agent alone. These effects seem to require cyclooxygenase products, and suggest that intravenous cyclooxygenase inhibitors may be of therapeutic value in patients with IL-1/TNF-mediated shock.